Leaching Behaviour of Synthetic Leachate through a Sewage Sludge and Red Gypsum Composite as Intermediate Landfill Cover - Nor Azalina, Rosli; Hamidi, Abdul Aziz; Ahmad Kueh, Beng Hong; Lim, Leonard Lik Pueh; Mohd Hafiz, Zawawi (MDPI, 2023)
This paper examines the environmental impact of the use of compacted sewage sludge: red gypsum (SS:RG) mixture as intermediate landfill cover in terms of yield and quality of leachate as characterised by hydraulic conductivity and leaching behaviour. A series of column tests using the constant head method is carried out by percolating the synthetic leachate through samples that have been compacted at various degrees (60, 70, 75, 80 and 85%). The leachate quality is monitored at pre-determined days for pH, COD, Cu, Fe and Zn. In general, hydraulic conductivity decreases in three stages, in which the first stage is mainly attributed to the particle rearrangement and hydration of calcium silicate hydrate (CSH). The hydration of CSH increases the pH, which causes the heavy metal to precipitate and be entrapped within the matrices of CSH gel, thereby further reducing the porosity and hydraulic conductivity. A minimum of 75% compaction has shown favourable final porosity, hydraulic conductivity, and leachate quality, although a minimum of 80% compaction is recommended in order to achieve a satisfactory compressive strength of greater than 345 kPa for a landfill operation.